1993
DOI: 10.1267/ahc.26.303
|View full text |Cite
|
Sign up to set email alerts
|

Method for Detecting the Expression of Bone Matrix Protein by in situ Hybridization Using Decalcified Mineralized Tissue.

Abstract: The sensitive and high resolution method of in situ hybridization technique has been developed using digoxigenin-11 UTP labeled cRNA as a probe. The system was applied to the decalcified mineralized tissues such as bone and dentin. Using the system, the localization of the mRNA of bone extracellular matrix proteins, osteopontin (Osp), osteonectin (Osn), Osteocalcin (Osc) and matrix Gla protein (MGP) was examined in decalcified bone. Decalcified femurs and mandibulae of embryo, neonatal, 2 to 40-week old mice w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 20 publications
(7 reference statements)
1
31
0
Order By: Relevance
“…The source of these proteins appeared to be through their synthesis and secretion by cells that had acquired an osteogenic phenotype. Osteopontin is a major non-collagenous protein in the bone matrix and is expressed by bone-related cells including osteoclasts, osteoblasts, and osteocytes (Nomura et al, 1993;Nanci et al, 1996). In the present study, osteopontin expression was recognized in the calcified matrix and in transforming cells after 4 weeks of transplantation.…”
Section: Discussionsupporting
confidence: 55%
“…The source of these proteins appeared to be through their synthesis and secretion by cells that had acquired an osteogenic phenotype. Osteopontin is a major non-collagenous protein in the bone matrix and is expressed by bone-related cells including osteoclasts, osteoblasts, and osteocytes (Nomura et al, 1993;Nanci et al, 1996). In the present study, osteopontin expression was recognized in the calcified matrix and in transforming cells after 4 weeks of transplantation.…”
Section: Discussionsupporting
confidence: 55%
“…13,14 The cRNA probes for in situ hybridisation of mouse ␣1 type-I collagen and ␣1 type-II collagen were given by Metsäranta et al 15 These were used after homology between mouse and rat cRNA had been confirmed by northern blotting. Type-X collagen cDNA was obtained by reverse transcription of mRNA from newborn rat bone tissue, followed by a polymerase chain reaction and subcloning into EcoRV site of pBluescript KS-(Stratagene, La Jolla, California).…”
Section: Methodsmentioning
confidence: 99%
“…Sense and antisense digoxigenin-labeled riboprobes were used as previously described (Nomura et al, 1993;Sawitzke et al, 2005). Probes were synthesized from chick Pdgfra clones (ChEST55k2) and from chick Pdgf-a ligand clones (ChEST826l7).…”
Section: In Situ Hybridizationmentioning
confidence: 99%